An ultrasound activated cyanine-rhenium(i) complex for sonodynamic and gas synergistic therapy. Issue 20 (18th February 2022) - Zhu, Jiayi; Ouyang, Ai; He, Jiaqi; Xie, Juan; Banerjee, Samya; Zhang, Qianling; Zhang, Pingyu
Abstract : The first example of a rhenium(i ) complex for tumor treatment through the synergism of SDT and gas therapy. Abstract : A novel cyanine-rhenium(i ) tricarbonyl complex is developed as a potent sonosensitizer and sono-activatable CO-releasing agent for synergistic sonodynamic therapy and CO gas therapy of cancer. The complex induced ferroptosis as the mode of cell death.